RETRACTED: Decision making in agricultural organizations: integral assessment methodology - Babkin Alexandr; Burkaltseva Diana; Kirilchuk Svetlana; Apatova Natalia; Vorobyova Elena; Borsch Lyudmila; Nalivaychenko Ekaterina; Blazhevich Oleg; Guk Olga; Bondarenko Daniil; Osmanova Elnara; Polskaya Svetlana; et al. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001